TRANSACTION COST, AGENCY THEORY, DAN STAKEHOLDER THEORY DALAM TEORI (DESAIN) ORGANISASIONAL: KAJIAN ASUMSI-ASUMSI DASAR - GAGARING PAGALUNG (Jurnal Bisnis dan Akuntansi, 2004)
This paper is to provide three perspectives on organizations recently have been the object of increasing interest: Transaction Cost, Agency Theory, and Stakeholder Theory. This reviews of organization concepts and basic assumptions, where is underlying why three perspectives not be integrated within each other. The main difference of these perspectives is Stakeholder Theory has moral principles or deontological base as a normative theoretical, while two others are not accommodated their principle.